2021
DOI: 10.3390/molecules26051224
|View full text |Cite
|
Sign up to set email alerts
|

Improving Blind Docking in DOCK6 through an Automated Preliminary Fragment Probing Strategy

Abstract: Probing protein surfaces to accurately predict the binding site and conformation of a small molecule is a challenge currently addressed through mainly two different approaches: blind docking and cavity detection-guided docking. Although cavity detection-guided blind docking has yielded high success rates, it is less practical when a large number of molecules must be screened against many detected binding sites. On the other hand, blind docking allows for simultaneous search of the whole protein surface, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Graziano reported that the non-intrinsic volumetric contribution at infinite dilution in water for mixture of hard spheres is always a small and positive quantity ( Graziano, 2006 ). We have recently confirmed this for model globular proteins ( Awoonor-Williams and Abu-Saleh, 2021 , Jofily et al, 2021 ). This is because this contribution to is the result of a balance between the repulsive volumetric component and the attractive component [see Eq.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Graziano reported that the non-intrinsic volumetric contribution at infinite dilution in water for mixture of hard spheres is always a small and positive quantity ( Graziano, 2006 ). We have recently confirmed this for model globular proteins ( Awoonor-Williams and Abu-Saleh, 2021 , Jofily et al, 2021 ). This is because this contribution to is the result of a balance between the repulsive volumetric component and the attractive component [see Eq.…”
Section: Resultssupporting
confidence: 63%
“…The interaction from the specific and non-specific van der Waals forces of water as a solvent with the polar, non-polar and charged surface residues of the protein is quantified in the attractive volumetric contribution (see (14) , (16) ) to the partial or apparent molar volume . This volumetric quantity therefore is a measure of the contraction of the volume of water as a solvent in the proximity of the charged, and polar groups of the protein ( Ball, 2017 , Fleming and Fleming, 2018 , Jofily et al, 2021 , Kaur et al, 2021 ). Hence its importance to evaluate the induced changes in protein hydration due to ligand binding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A classical docking validation through re-docking an experimental ligand-protein complex cannot be therefore carried out in this case. In contrast to a "focused" docking targeted to an already known binding site, our docking calculations can be considered as "blind" docking [69][70][71][72][73][74].…”
Section: Computational Detailsmentioning
confidence: 99%
“…Blind docking is an approach used to determine ligand binding sites and best ligand conformation in ligand-receptor interactions. 29 This technique is well suited for small protein targets and single ligand docking. It permits screening of the total area of the query protein to identify best residues with strongest interaction and best ligand conformation.…”
Section: Resultsmentioning
confidence: 99%